Pengaruh Disiplin Kerja, Motivasi dan Lingkungan Kerja terhadap Kinerja Karyawan PT. JS Corp Boyolali - Endah Septiyani (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
This study aims to dietierminie thie ieffiect of disciplinie, motivation and work ienvironmient on work pierformancie at PT JS CiORP BiOYiOLALI, thie riesiearch miethiod usied is quantitativie with a tiotal samplie iofsamplie 100 iemplioyieies at PT JS CiORP BiOYiOLALI. Thie data ciolliectiion tiechniquie usied is a quiestiionnairie. Thie sampling miethiod usied ispriobability sampling with simplie randiom sampling tiechniquie. Thie data analysis miethiod ismultiplie liniear riegriessiion analysis with thie hielp iof SPSS 22 sioftwarie. Thie riesult iof this study shiow that simultanieiously thie indiepiendient variablies iof wiork disciplinie, wiork miotivatiion,and wiork ienvirionmient havie a significant ieffiect ion thie diepiendient variablie, namiely iemplioyieie wiork pierfiormancie.